TAX EVASION AND BLACK MONEY IN INDIA: CAUSES AND SOLUTIONS - Kethankar B R (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study explores the causes, extent, and impacts of tax evasion and black money in India, supported by statistical data and real-world case studies. It also critically examines the effectiveness of existing solutions and suggests policy reforms to address these deeply rooted economic and governance issues. Tax evasion and black money have been persistent and deeply entrenched challenges for the Indian economy, undermining fiscal stability, economic development, and social equity. Tax evasion refers to the illegal practice of deliberately avoiding the payment of taxes through concealment of income, manipulation of accounts, or exploitation of legal loopholes. Black money, on the other hand, denotes income that is undisclosed to tax authorities, often generated through unreported legitimate earnings or illegal activities such as corruption, smuggling, and bribery. Together, these phenomena erode government revenues, fuel inflation, distort investment patterns, and widen income inequalities. The causes of tax evasion and black money generation in India are multifaceted. They include high tax rates in the past, complex and ambiguous tax laws, the dominance of the informal sector, widespread use of cash transactions, political corruption, and weak enforcement mechanisms. The real estate sector, unorganised trade, shell companies, and offshore tax havens are key contributors to the problem. Social tolerance towards tax evasion and a lack of trust in government spending further aggravate the situation. To combat these issues, the Indian government has implemented several measures, including tax reforms like the Goods and Services Tax (GST), the demonetisation of high-value currency notes, increased digitisation of financial transactions, stricter monitoring of foreign assets, and legal frameworks like the Black Money (Undisclosed Foreign Income and Assets) Act, 2015. Despite these efforts, tax evasion and black money continue to pose significant policy challenges due to the complexity and scale of the problem.